New Advances in Sultine Chemistry - Zhu, Zhiming; Deng, Zhengxi; Ouyang, Xinke; Shu, Chao (Synlett, 2023)
Sultines (lactones of sulfinic acids), as a fascinating class of sulfur heterocycles, has been found tremendous applications in the field of chemistry, pharmaceutical, and materials sciences due to the unique chemical, biological, and pharmaceutical activities. However, the chemistry of sultines long remains less developed because of their challenging to access with traditional routes. The recent years have witnessed an increasing interest in sultines preparation and new methods were reported with modern methodologies and technologies. The main objective of this Synpacts article is to summarize the latest major developments for the synthesis of sultine frameworks/ring systems, mainly covering radical relay, anion relay cyclization and radical anion relay cyclization. We wish to bring readers a comprehensive understanding about the state of play of sultines formation and make contribution for future research.1 Introduction2 Radical Relay Cyclization3 Anion Relay Cyclization4 Radical Anion Relay Cyclization5 Conclusion
Keywords: sultines; photocatalysis; cyclization; radical; anion